The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00248-010-9664-z
|View full text |Cite
|
Sign up to set email alerts
|

An Antarctic Hot Spot for Fungi at Shackleton's Historic Hut on Cape Royds

Abstract: The historic expedition huts located in the Ross Sea Region of the Antarctic and the thousands of artifacts left behind by the early explorers represent important cultural heritage from the "Heroic Era" of Polar exploration. The hut at Cape Royds built by Ernest Shackleton and members of the 1907-1908 British Antarctic Expedition has survived the extreme Antarctic environment for over 100 years, but recent studies have shown many forms of deterioration are causing serious problems, and microbial degradation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 27 publications
1
60
1
Order By: Relevance
“…That these were common to soils but not to rocky niches offers further evidence that they have been selected for on this basis, because rocky niches are not reservoirs for the "legacy" carbon that is known to endure in Antarctic soils (4). Our results of lignin-like degradative pathways are supported by the findings of wood-degrading fungi in a wide variety of Antarctic soils (20,61,62). A link has been suggested between these saprophytic fungi and those found in the fossil record of the Triassic and Jurassic forests of Antarctica (61).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…That these were common to soils but not to rocky niches offers further evidence that they have been selected for on this basis, because rocky niches are not reservoirs for the "legacy" carbon that is known to endure in Antarctic soils (4). Our results of lignin-like degradative pathways are supported by the findings of wood-degrading fungi in a wide variety of Antarctic soils (20,61,62). A link has been suggested between these saprophytic fungi and those found in the fossil record of the Triassic and Jurassic forests of Antarctica (61).…”
Section: Discussionsupporting
confidence: 78%
“…A link has been suggested between these saprophytic fungi and those found in the fossil record of the Triassic and Jurassic forests of Antarctica (61). Fungi are notorious contaminants especially on imported materials and around sites of human activity and the difficulty of discerning transient/introduced vs. indigenous and endemic organisms and their input to the environment is acknowledged, although indigenous and not exotic fungi dominate on imported wood (62). The structural similarities between lignins and other naturally occurring complex organics and many xenobiotic compounds led us to propose that because of the presence of these fungi, Antarctic soils may possess an innate ability to respond to future pollution threats from these compounds (38).…”
Section: Discussionmentioning
confidence: 99%
“…Blanchette et al (2004) first reported an unusual form of soft rot decay caused by Cadophora species which can cause degradation of the historic huts and artefacts. This type of decay has subsequently been found to be prevalent in historic woods and in soils from the immediate vicinity of the huts at many Antarctic locations and variety of filamentous fungi and yeasts such as Cadophora, Cladosporium, Cryptococcus and Geomyces species were discovered with a high frequency (Arenz et al 2006; Arenz and Blanchette 2009; Blanchette et al 2010). Although there are few woody plants on the Antarctic continent, researches provide strong evidence that Antarctic fungi are able to colonise and degrade-introduced wood and other organic materials (Blanchette et al 2004, 2010).…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…This type of decay has subsequently been found to be prevalent in historic woods and in soils from the immediate vicinity of the huts at many Antarctic locations and variety of filamentous fungi and yeasts such as Cadophora, Cladosporium, Cryptococcus and Geomyces species were discovered with a high frequency (Arenz et al 2006; Arenz and Blanchette 2009; Blanchette et al 2010). Although there are few woody plants on the Antarctic continent, researches provide strong evidence that Antarctic fungi are able to colonise and degrade-introduced wood and other organic materials (Blanchette et al 2004, 2010). Held et al (2005) found that Antarctic summer above 0°C and 75% relative humidity occurred for many weeks, which are conducive for fungal growing inside the historic huts on Ross Island.…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
See 1 more Smart Citation